Integrating landscape ecological risk into ecosystem service value assessment: A case study of Nanjing City, China - Liang-Jie Wang; Gui-Yin Luo; Shuai Ma; Hui-Yong Wang; Jiang Jiang; Jian-Gang Zhang (Ecological Indicators, 2023)
The scientific assessment of ecosystem service value (ESV) and landscape ecological risk (LER) is important for ecological security and sustainable development. However, existing studies often separate ESV and LER for a single evaluation, and the single evaluation is limited in guiding ecological conservation. Therefore, proposing an evaluation framework that integrates ESV and LER is urgent. Taking Nanjing City as an example, this study evaluated LER based on the risk evaluation cell and introduced it into ESV evaluation. Then, the influence of land use/land cover change on LER and ESV from 2000 to 2020 was analyzed. The results showed that built-up land and water body/wetland increased by 881.96 km2 and 41.41 km2, and farmland and forest land decreased by 875.46 km2 and 55.83 km2 from 2000 to 2020. The LER was low in the middle and high in the north and south. From 2000 to 2010, the LER increased from 0.67 to 0.68, and it then decreased to 0.61 in 2020. Medium-low risk regions decreased during 2000–2010, and low-risk regions increased and medium-high risk regions decreased during 2010–2020. The ESV increased by 0.77 billion United States dollars (USD) during 2000–2010 but decreased by 0.40 billion USD during 2010–2020. Under the impact of LER, the ESV per unit area of the farmland, forest land, and water body decreased during 2000–2020. The ESV of the water body dominated the total ESV and had an important influence on the change in total ESV. The ESV in Nanjing City during 2000–2020 mainly showed High-High autocorrelation and a few Low-High autocorrelations. Ecological restoration programs increased ESV during 2000–2010, but rapid urbanization reduced ESV during 2010–2020. Integrating social, economic, and ecological resources is necessary to realize the coordinated development of the economy and ecology. The results can provide an important reference for landscape planning and ecosystem management.